Evaluating Cercospora leaf blight resistance in soybean accessions using an improved categorical disease-evaluation scale. Issue 5 (3rd September 2021) - Ward, Brian M.; Shrestha, Bishnu K.; Allen, Tom W.; Buckley, Blair; Chen, Pengyin; Clubb, Michael; Mozzoni, Leandro A.; Orazaly, Moldir; Florez, Liliana; Moseley, David; Rupe, John C.; Gentimis, Thanos; et al.
ABSTRACT: Cercospora leaf blight (CLB), caused by Cercospora kikuchii, C . cf. flagellaris, and C . cf. sigesbeckiae, is a serious disease of soybean [ Glycine max (L.) Merr.], which is prevalent in the mid-southern and southeastern USA, where hot and humid conditions prevail during the growing season. Few resistant soybean cultivars have been identified, as previous evaluations across time and location have been notoriously inconsistent because of variable pathogen diversity and environmental conditions. To confound management options, the pathogens have developed resistance to quinone outside inhibitor fungicides and fungicides that contain thiophanate-methyl as an active ingredient. Soybean accession lines (n = 568), representing maturity groups III to VII, were planted across the southeastern USA and evaluated for the presence and severity of naturally infected CLB during 2016 and 2017 based upon multiple evaluation scales. Good correlations between symptom types allowed for unification of multiple scales into a single evaluation scale that was used in 2018. Evaluation scales were converted to categorical data and compared to search for accessions that exhibited consistent resistance to the disease. In this study, >50 accessions were identified with resistance to CLB. In addition, a new evaluation scale described herein allows for fast and accurate evaluation of large-scale field experiments for CLB across multiple locations.